Enhancing Arabic Vocabulary Retention Through the Drill Method: A Study on Sixth-Grade Students' Memorization Skills - Al Farozi; Hadawiyah, Rabiatul; Aminudin; Hasanah, Nur (Journal of Educational Management Research, 2025)
This study aimed to improve the Arabic vocabulary memorization skills of seventh-grade students at MI Nasy’atul Muta’allimin through the implementation of the drill method. Arabic language learning, particularly vocabulary acquisition, remains a significant challenge, especially in religious educational contexts where fluency is essential for understanding religious texts. The research employed a Classroom Action Research (CAR) design with a descriptive quantitative approach, focusing on two cycles of planning, implementation, observation, and reflection. Data was collected using observation, tests, interviews, and documentation. The results showed a clear improvement in students' vocabulary memorization, with average scores rising from 62.1 in the pre-cycle to 82 in the second cycle, and the percentage of classical completion increasing from 35% to 80%. Interviews revealed increased student motivation and engagement. The study concludes that the drill method effectively enhances Arabic vocabulary retention and student enthusiasm. The contribution of this research lies in providing evidence for the effectiveness of active learning strategies in language acquisition, specifically in religious education settings, and offering practical solutions for language teachers.